Nazhir Capacity Building in Waqf Management Through The Nazhir Waqf Certification Program in East Java - Faujiah, Ani; Hamidiyah, Emmy (Proceedings of Annual Conference on Community Engagement, 2022)
The province of East Java has a total amount of waqf  land covering an area of 58,239,272 M2, a great potential in helping the community's economy by empowering waqf assets, making waqf more productive and can contribute to economic growth. In the discussion of representation, it focuses not only on how to hold property eternal but how nazhir as a manager can develop waqf in productive activities so that it can continue to generate benefits. From several research results, it was found that there were three main problems with nazhir, namely low competence in management, not as the main profession, and waqf management was not optimal. The nazhir waqf certification program is one of the efforts to increase the capacity of Nazhir. The approach used is action research, by actively involving all relevant parties.